MISE EN ŒUVRE D’UNE ANALYSE INFORMATIQUE DE GESTION DU PERSONNEL MILITAIRE DANS UNE ZONE DE DEFENSE CAS DE LA 31EME REGION MILITAIRE KISANGANI VILLE - NGONGO , Faysal BAONGA; MUTSUVA , Christian NZANZU (IJRDO -Journal of Computer Science Engineering, 2023)
Computers are emerging as a new way of organizing work that best meets the needs of a society seeking its way to a new type of growth. The main interest in computers is their ability to store information and perform complex calculations and operations in record time. The problem of managing military personnel within the 31st military region is fraught with enormous difficulties, some of which are as follows: slowness in searching for military personnel files; enormous difficulties in drawing up lists of military personnel according to selection criteria; risk of data loss in the archiving process; risk of confidential data being altered by unauthorized persons; enormous difficulties in drawing up attendance lists; etc. This theme has a particular objective for military records management, that of implementing a computerized analysis system to accommodate the requirements of new technology. In view of all these difficulties, we believe that the current management system could be improved by integrating a computerized solution based on the implementation of a computer analysis methodology based on the MERISE method. Today, the world is undergoing a major transformation, an unprecedented scientific evolution in the field of information technology.